Madrasa Principal's Managerial Skills: Its Influence On Madrasah Climate And Teacher Motivation - Widyaswara, Imelda Ayu (Journal of Advanced Islamic Educational Management, 2023)
The problems in this study: (1) Is The the madrasa head's managerial skills affect teacher performance? (2) Is The madrasa climate affect teacher performance? (3) Is The motivation affect teacher performance? (4) Is The madrasa principal's managerial skills, madrasa climate, and work motivation jointly influence performance? The research objectives (1) determine the effect of the madrasa principal's managerial skills on teacher performance. (2) determine the effect of madrasa climate on teacher performance. (3) determine the effect of teacher work motivation on teacher performance. (4) to determine the effect of the skills of the madrasa headmaster, madrasa climate and teacher work motivation together on teacher performance. This research uses Quantitative method. The population is 105 teachers, the sample is 21 teachers. Data collection techniques in this study, questionnaires, observation, linear analysis techniques. The results of this study: (1) There is an influence of the madrasa head's managerial skills on teacher performance. (2) There is an influence of the madrasa climate on teacher performance. (3) There is a positive influence of work motivation on teacher performance. (4) There is a positive influence on the managerial skills of madrasa headsmaster, madrasa climate, and work motivation together on teacher performance.